Pedagogical excellence of foreign language teachers in the educational process on the basis of innovative information technologies (Pedagogy of Higher and Secondary Education, 2014)
Poberezhna N. O. Pedagogical excellence of foreign language teachers in the educational process on the basis of innovative information technologies.The article deals with didactic and methodological aspects of modern pedagogical system and pedagogical activity in teaching foreign languages in the conditions of educational information environment. The information and communication competence of the teacher is argued anddefined as the willingness and ability to use didactic potential of information and communication technologies methodically and competently in teaching activities under EIE. A complex of professional competencies including information competence of foreign languages teachers is presented to meet urgent needs for effective teaching of foreign languages.
Keywords: pedagogical excellence; information competence; educational information environment of higher educational establishment